Spectral-Domain Optical Coherence Tomographic Assessment of Severity of Cystoid Macular Edema in Retinopathy of Prematurity - Maldonado, Ramiro S. (2012)
OBJECTIVE: To investigate whether the severity of cystoid macular edema (CME) in neonates who were 31 to 36 weeks’ postmenstrual age, as viewed by spectral-domain optical coherence tomography (SD-OCT) imaging, predicts the severity of retinopathy of prematurity (ROP) or is related to systemic health. DESIGN: Of 62 prematurely born neonates in a prospective institutional review board–approved study, 42 met the following inclusion criteria: at least 1 SD-OCT imaging session prior to 37 weeks’ postmenstrual age and prior to ROP laser treatment, if a laser treatment was performed, and an ophthalmic ROP examination at or after 41 weeks’ postmenstrual age, evidence of complete retinal vascularization in zone III, or documentation through telephone report of such information after transfer of care. Measures of CME severity, including central foveal thickness, retinal layer thicknesses, and foveal-to-parafoveal thickness ratio in 1 eye per subject, were compared with ROP outcomes: laser treatment, maximum plus disease, and maximum ROP stage. Systemic health factors were also correlated. RESULTS: Cystoid macular edema was present in 50% of neonates. Multiple elongated cystoid structures within the inner nuclear layer were most common. The presence of CME was not associated with ROP outcomes. The central foveal thickness, the thickness of the inner retinal layers, and the foveal-to-parafoveal thickness ratio were higher in eyes that required laser treatment or that developed plus disease or ROP stage 3. Cystoid macular edema was not clearly associated with systemic factors. CONCLUSIONS: Cystoid macular edema is common in premature infants screened for ROP before 37 weeks’ postmenstrual age, with the most common SD-OCT phenotype of a bulging fovea from multiple elongated cystoid spaces. Detection of CME is not associated with ROP severity; however, tomographic thickness measurements could potentially predict a higher risk of requiring laser treatment or developing plus disease or ROP stage 3. Systemic health factors are probably not related to the development of CME.